2016
DOI: 10.1159/000445606
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Periostin Prevents High Glucose-Induced Mitochondrial Apoptosis in Human Umbilical Vein Endothelial Cells via Activation of Nrf2/HO-1 Signaling

Abstract: Background/Aims: High glucose-induced oxidative damage to endothelial cells plays a central role in the pathogenesis of diabetic vascular complications. This study was undertaken to explore the role of periostin in high glucose-induced endothelial cell apoptosis and associated molecular mechanisms. Methods: Human umbilical vein endothelial cells (HUVECs) were exposed to high glucose (33.3 mmol/L) and examined for the expression of periostin. The effects of periostin upregulation on high glucose-induced apoptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…Several studies have shown that other adhesion molecules, such as VE-cadherin and PECAM-1 (CD31), can be modulated by TRPM4 [28] and TRPM7 [29]. Endothelial dysfunction is a complex and multistep process that includes endothelial cell migration [30-33]. Our data clearly demonstrate that H 2 O 2 considerably promotes EC migration and that inhibition of TRPM4 with 9-phenanthrol significantly inhibits H 2 O 2 -induced migration of HUVECs.…”
Section: Discussionsupporting
confidence: 57%
“…Several studies have shown that other adhesion molecules, such as VE-cadherin and PECAM-1 (CD31), can be modulated by TRPM4 [28] and TRPM7 [29]. Endothelial dysfunction is a complex and multistep process that includes endothelial cell migration [30-33]. Our data clearly demonstrate that H 2 O 2 considerably promotes EC migration and that inhibition of TRPM4 with 9-phenanthrol significantly inhibits H 2 O 2 -induced migration of HUVECs.…”
Section: Discussionsupporting
confidence: 57%
“…Conversely, periostin inhibits glucose-induced ROS production in endothelial cells (316). Growth of human umbilical vein endothelial cells in medium containing 33 mM glucose for 2 days induced periostin expression and apoptosis.…”
Section: B Periostinmentioning
confidence: 95%
“…The activity of caspase-3 was detected by a colorimetric caspase-3 assay kit (Sigma, St. Louis, MO, USA) according to the manufacturer's protocol [20]. HCAECs (2 × 10 5 /well) were cultured in 6-well plates with QL (0-1 µg/ml) and ox-LDL (150 μg/ml) for 24 h. The cell lysate were added with caspase-3 substrate at 37°C for 90 min.…”
Section: Measurement Of Caspase-3 Activitymentioning
confidence: 99%